Corrosion resistance of plasma nitrided tool steel at variable temperature and time (Indian Journal of Chemical Technology (IJCT), 2025)
Wood machining steel has been nitrided with the view to enhance the corrosion resistance properties. Nitriding is performed by varying the time and temperature in the nitrogen and hydrogen plasma. Steel samples after polishing are kept inside the nitriding reactor and biased at -250 V to attract the nitrogen and hydrogen ions. Nitrided and bare steels were then subjected to X-ray diffraction (XRD) for the phase analysis. The presence of FexN (where x = 2-3, 4) is observed after XRD analysis.Corrosion resistance of the bare and nitrided steels is assessed by following potentiodynamic polarization tests at room temperature in 3.5 wt.% NaCl solution. Field emission electron microscopic analysis (HRFE-SEM) of the corroded surface revealed pittings more on the surface of the bare steel than that on the nitrided steels. Finally, it has been concluded that corrosion resistance of nitrided steels was significantly improved when compared to that of the bare steel due to the formation of Fe-nitrides after nitriding.